Notification of crop varieties and registration of germplasm - Patnaik et al, A. (The Indian Journal of Genetics and Plant Breeding, 2016)
Notification of crop varieties and registration of germplasmÂ Rice :CR Sugandh Dhan 907Poornabhog (CR Basna Dhan 902)Nua Kalajeera, Nua Dhusara and Nua Chinikamini